Problem Tree as a Methodology to Identify Causes and Effects of Complex Systems - Jimenez-Galina, Alicia Margarita; Olmos-Sanchez, Karla Miroslava; Maldonado-Macaas, Aide Aracely; Garnica-Gonzalez, Jaime; Licona-Olmos, Jazmin Georgina (2023 12th International Conference On Software Process Improvement (CIMPS), 2023)
A complex system is characterized by having multiple interconnected and interdependent components, whose global behavior arises from the dynamic interaction between them. When a complex system does not have a clear and defined structure to organize the information, it is a Complex System in an Informally Structured Domain. The inadequate characterization of this kind of systems leads to the generation of negligent and insufficient solutions that do not support effective decision making. The objective of this research is to identify the causes and effects of a complex system in informally structured domains, through the application of the participatory technique of the cause-effect problem tree. As a result, the cause-effect problem tree diagram of a Complex System in an Informally Structured Domain is developed, which clearly and concisely identifies the causes and effects related to the problem and the consequences associated with them. It is concluded that the application of the problem tree technique is an adequate tool to identify causes and effects even in complex realities such this kind of systems.